Evaluation of the JAK2V617F Mutational Burden in Patients with Philadelphia Chromosome Negative Myeloproliferative Neoplasms: A Single-center Experience - Popova-Labachevska M; Panovska Stavridis I; Eftimov A; Kapedanovska Nestorovska A; Cevreska L; Ivanovski M; Ridova N; Trajkova S; Dimovski AJ (Macedonian Academy of Sciences and Arts / Sciendo, 2019)
The identification of the JAK2V617F mutation in several distinct myeloproliferative neoplasms (MPNs) raised the question how one single mutation incites expression of at least three different clinical phenotypes, i.e., polycythemia vera (PV), essential thrombocythemia (ET) and primary myelofibrosis (PMF). In order to further evaluate already published data on the correlation between mutant JAK2V617F allele burden and specific hematological and clinical parameters, we tested the level of the JAK2 mutation in 134 JAK2+ patients with different MPNs. The patients were diagnosed according to the 2008 WHO criteria and followed for a median of 48 months. The JAK2 V617F quantification was done with a real time polymerase chain reaction (real time-PCR) method. The median allele burden was lowest in ET (25.8%), followed by 34.6% in PV and 51.8% in PMF patients (p<0.01). There was statistically significant association between the mutational load of 10.0-50.0% and blood count parameters in the PV patients (p<0.05). In PMF patients the mutational load was in correlation with older age and leukocyte count that were higher in patients with the mutational load of 10.0-50.0% and >50.0% compared to those with a mutational load of <10.0%. There were no statistically significant associations between the allele burden and blood counts in the ET cohort. Our study confirmed an association between the JAK2V617F allele burden and the distinct MPN phenotypes, indicating unfavorable prognosis in patients with a higher JAK2 allele burden. Our results suggest that JAK2 quantification should be incorporated in the diagnostic work-up of MPN patients as a useful tool for optimal treatment decision.
Keywords: allele burden; JAK2V617 mutation; myeloproliferative neoplasms (MPNs)